Assessing the Impact of Qonun Aceh No. 11 of 2018 Concerning Sharia Financial Institutions: Dynamics of Sharia Banking Financial Performance in Aceh Province - Purwanto, Purwanto; Dasuki, Ali Ibrahim; Rokhmadi, Rokhmadi; Sam’ani, Sam’ani (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Qanun Aceh No. 11 of 2018 mandates that all financial institutions transition to Sharia financial systems. The enactment of this Qanun has led to shifts in market dynamics and increased public trust in Sharia financial institutions. Consequently, this study aims to examine the impact of Qanun Aceh No. 11 of 2018 on the financial performance of Sharia banking in Aceh Province. The research employs a quantitative approach, utilizing secondary data published by the Financial Services Authority. The data pertains to key financial performance indicators of Sharia banking, including assets, financing, and third-party funds, both before and after the implementation of Qanun Aceh No. 11 of 2018. The data is analysed using paired sample t-tests. This research shows that the enactment of Qanun Aceh no. 11 of 2018 is the expected consequence of the existence of a Sharia banking monopoly in the region. This research shows that the enactment of Qanun Aceh no. 11 of 2018 is the expected consequence of the existence of a Sharia banking monopoly in the region. This policy forces all customers, whether individuals, businesses, corporations, or local government funds, to move their accounts from conventional banks to Sharia banks. Thus, the increase in Sharia banking assets and funds is more the result of the relocation of funds previously in conventional banks, not solely due to an increase in public preference for the Sharia financial systems. This finding highlights that the Qanun has enhanced public participation and trust in Sharia banking. The study provides crucial insights into the role of regulations in fostering the development of Sharia banking.